2020
DOI: 10.1557/mrc.2020.70
|View full text |Cite
|
Sign up to set email alerts
|

Rugged nanoparticle tracers for mass tracking in explosive events

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…[1][2][3] The authors have reported previously on the survivability of ruggedized particulate tracers during explosions. [4] Present results inform the survivability of silica-coated luminescent tracer particles in the environment as well as synthesis paths to control particle size while maintaining luminescent intensity. The ability to control particle size and emissive color, and to ensure the tracer's long-lasting endurance provides an elegant solution for tracking mass through harsh environments.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…[1][2][3] The authors have reported previously on the survivability of ruggedized particulate tracers during explosions. [4] Present results inform the survivability of silica-coated luminescent tracer particles in the environment as well as synthesis paths to control particle size while maintaining luminescent intensity. The ability to control particle size and emissive color, and to ensure the tracer's long-lasting endurance provides an elegant solution for tracking mass through harsh environments.…”
Section: Introductionsupporting
confidence: 52%
“…In previous work, shielding zinc sulfide (ZnS:Mn) quantum dots in 100-nm-thick silica shells lead to a two-to-three-fold increase in luminescent intensity post-explosion when compared to bare quantum dots. [4] As previously reported results have explored the ruggedization of silica-covered ZnS:Mn quantum-dot tracers, this work expands the scope to explore the environmental endurance of the ruggedized tracers.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations